The Role of Geospatial Engineering in Handling Natural Disasters and Humanitarian Crises - Thandar Htwe; Soe Thu Zaw; Arnes Yuli Vandika (Yayasan Adra Karima Hubbi, 2024)
The background of this research is the increasing frequency and intensity of natural disasters and humanitarian crises that require rapid and effective handling. Geospatial techniques have emerged as an important tool in disaster management, offering solutions for real-time mapping, monitoring, and analysis of emergency situations. The purpose of this research is to evaluate the role and effectiveness of geospatial techniques in handling natural disasters and humanitarian crises, and to identify areas that need improvement. The research method used involves analysis of current literature and case studies of various natural disaster incidents and humanitarian crises around the world. Data is collected from reliable sources such as scientific journals, government reports, and non-governmental organizations. This approach allows researchers to evaluate the practical application of geospatial techniques and identify key factors that influence their success. The results of the study show that geospatial techniques play a vital role in various stages of disaster management, from mitigation, preparedness, response, to recovery. Risk mapping, environmental change monitoring, and spatial analysis have been shown to improve the efficiency and effectiveness of emergency response operations. However, the study also identified challenges such as limited data access, the need for specialized training, and adequate technological infrastructure.The study’s conclusion confirms that geospatial techniques are a crucial component in managing natural disasters and humanitarian crises. Proper implementation can save lives and significantly reduce negative impacts. Therefore, investment in geospatial technologies, human resource training, and infrastructure development should be a priority to improve emergency response capacity in the future.